Assessment of nanofluid on the performance and energy-environment interaction of Plate-Type-Heat exchanger. (1st October 2021) - Jassim, Esam I.; Ahmed, Faizan
Highlights: Both nanofluid improve the performance of the Plate-Type heat exchanger. Effectiveness of PHE ameliorates with the increase in Reynolds number. Aluminum Oxide enhances PHE performance better than Titanium Oxide. Heat Leak to atmosphere directly proportions to Re for both nanofluids. Particle concertation improves the exchanger effectiveness but increases the heat leak. Abstract: Upgrading the performance of the heat exchanger by ameliorating the thermal properties of the working fluid can be achieved by mixing nano-sized solid particles with the base fluid. The present study reports the impact of mixing metallic oxide nanoparticles with distilled water on the heat transfer, heat loss, and effectiveness of Plate-type Heat Exchanger (PHE). A comparison of two types of particles, namely: TiO2 and Al2 O3 at various Volume Fractions (VoF) is experimentally evaluated. The effect of flow rate of the nanofluid and concentration of dispersed nanoparticles on the exchanger characteristic and performance is also addressed. A mathematical model is developed to process the experimental data of the pure fluid as well as the two nanofluids at various volume concentration and flowrates. The results show that the energy transfer between the two fluids is enhanced when nanofluid replaces the conventional fluid at a specified Reynolds number. The performance also ameliorates with augmentation in VoF of the nanoparticle. The outcome of the analysis also ascertains that Aluminum Oxide behaves better than Titanium Oxide in terms of improving PHE performance at relatively high Reynolds number. At Re ~ 15000, mixing 3% VoF of TiO2 with the base fluid increases the effectiveness of the exchanger by ~ 13% while the upgrade touches ~ 23% for same mixing fraction of Al2 O3 . The analysis of the current research shows that mixing 3% of Aluminum Oxide with distilled water could increase the heat leak factor up to 40% at Re = 12000 while at the same concentration of Titanium Oxide the heat leak factor approaches 45%. However, when the Reynolds number approaches 14000, the heat leak factor of Al2 O3 is almost doubled whereas the magnitude of TiO2 is barely augmented to 50%.